QUINOA AS A SUBSTITUTE FOR SEMOLINA: SOME ASPECTS AND PROBLEMS OF INTRODUCTION - Sergiy BORUK (Stefan cel Mare University of Suceava, 2017)
Semolina is one of the most widely used kinds of finely ground cereals, which is easy to digest and assimilate. However, it consists of significant amount of heavy gluten which is not suited for people suffering from celiac diseases. Besides, the content of proteins, vitamins and microelements in semolina is comparatively poor. Quinoa is a pseudo-grain crop imported mostly from South America. Quinoa can be considered as a substitute for semolina since it is rich in vitamins, proteins, amino acids and microelements, and targeted especially to the customers suffering from celiac disease, allergic to gluten or having special dietary requirements. It is important to investigate and compare some rheological properties of quinoa and semolina in order to ensure safe and effective interchanges in the technology of cereals production. It has been found that swelling of the quinoa mixtures is higher than that of the semolina mixtures. A rise in temperature causes initial increase in volume of the dispersed phase particles followed by fast destruction of the cereal disperse systems. Viscosity of the quinoa mixtures shows a sharp rise when mass percent of the cereal exceeds 13 % while in case of semolina mixtures, the same phenomenon occurs after 16 %. A rise in viscosity is unwanted since it lowers the quality of the material used. It can be avoided to some extent by partial substitution of semolina with quinoa as 1:0.8.